43. SOME FACTORS RELATED TO SIGNS OF DEPRESSION IN HYPERTENSIVE OUTPATIENTS AT HOE NHAI GENERAL HOSPITAL IN 2023 (Vietnam Journal of Community Medicine, 2025)
Objective: To identify factors related to signs of depression in hypertensive outpatients.Subject and method: A cross-sectional descriptive study was conducted on 379 outpatient hypertensive patients at Hoa Nhai General Hospital from October 24, 2023, to November 17, 2023. Patients were considered to have signs of depression if their depression score on the DASS-21 scale was 10 points or higher.Results: The prevalence of depressive symptoms was 14.8%. Factors associated with an increased risk of depression included age > 60 years (OR=2.22), hypertension treatment duration > 5 years (OR=1.90), comorbidities (OR=2.53), adverse effects from antihypertensive medication (OR=4.78), and inability to control blood pressure (OR=17.78).Conclusion: Age and hypertension-related factors are associated with depressive symptoms in patients. Therefore, hospitals should implement interventions based on these risk factors to reduce depression rates among patients.
Keywords: depression; hypertension